Plant Turnaround Maintenance in Malaysia Petrochemical Industries: a Study of Organizational Size and Structuring Processes - Halib, Mohammed (Intellectbase International Consortium, 2010)
Plant turnaround maintenance, a crucial asset management in petrochemical industries is carried out to revitalize, maintain, and improve the plant facilities for optimal and efficient performance. Large organizational resources comprising plant and maintenance personnel, technicians, craftsmen, skilled and specialist contractors and enormous magnitude of inter-related activities marked the complexity of the turnaround maintenance setting. The establishment of the appropriate configuration of organizational size and structuring processes are critical in organizing and managing the resources to ensure the success of the turnaround maintenance event. This paper discusses the relationship of organizational size and structuring processes in plant turnaround maintenance of 30 petrochemical companies in Malaysia. Six hypotheses were tested using bi-variate Pearson product-moment correlation. The test results provide the evidence that organizational size influences the organizational structuring processes of turnaround maintenance. The organizations of the turnaround maintenance are featured by high levels of centralization and formalization denoting the organization’s low level of tolerance on the variability of the behavior and performance of the organizational members